PERAN GREEN HUMAN RESOURCE MANAGEMENT DALAM MEMBENTUK PERILAKU KARYAWAN YANG MENDUKUNG EFISIENSI ENERGI DAN DIGITALISASI DI PT TECHNET VISION INDONESIA JAKARTA - Yunika Anggraini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital transformation has driven organisations to improve operational efficiency whilst integrating sustainability through the adoption of Green Human Resource Management (GHRM). Although PT Technet Vision Indonesia has utilised various digital technologies in its operational activities, the implementation of GHRM has not yet been systematically integrated into its human resource policies. This situation means that employee behaviour supporting energy efficiency and digitalisation is still influenced more by work culture and individual awareness than by structured organisational policies. This study aims to analyse the role of Green Human Resource Management in shaping employee behaviour that supports energy efficiency and digitalisation, to identify factors hindering its implementation, and to describe employee behaviour relating to energy efficiency and digitalisation at PT Technet Vision Indonesia. This study employs a qualitative approach using ethnographic methods. Data were collected through observation, in-depth interviews and documentation involving informants, Key Informantts and Expert Informants. Data analysis was carried out using domain analysis, taxonomic analysis, component analysis and cultural theme analysis. The research findings indicate that a digital work culture has evolved into a key characteristic of organisations, supporting communication, collaboration, productivity and data driven decision-making. However, the implementation of Green Human Resource Management (GHRM) is still in a transitional phase as it is not yet supported by integrated HR policies, standard operating procedures, environment-based performance indicators, or sustainable training programmes. Employee behaviour that supports energy efficiency and digitalisation is shaped more by the digital work culture and individual awareness than through the systematic application of GHRM. This study concludes that PT Technet Vision Indonesia already possesses a strong foundation of digital culture as a key asset in the development of Green Human Resource Management. Therefore, it is necessary to strengthen the integration of GHRM into human resource management policies and practices in order to consistently foster an organisational culture oriented towards sustainability, energy efficiency and digital transformation.